A comparison of salivary thiocyanate in cigarette smokers with and without oral leukoplakia: A biochemical study - Anshul Aggarwal; Neha Agrawal; Md Asdullah; Rati Goyal (Wolters Kluwer Medknow Publications, 2020)
Objective and Background: Determining SCN (thiocyanate) levels in saliva has been the most frequently used biochemical tests for establishing an incidence of tobacco consumption among smokers and can be used as biochemical indicator in the evaluation of precancerous condition like oral leukoplakia. Materials and Methods: Group A (n = 30) consisted of a clinically diagnosed case of oral leukoplakia between the ages of 30 and 50 years (n = 30) with inclusion criteria of male gender and history of cigarette smokers with a habit of smoking 4-7 cigarettes per day for a minimum period of 4-5 years or more. Group B, cigarette smokers without leukoplakia group, consisted of individuals (n = 30) with inclusion criteria of matched age and sex and history of cigarette smoking. The salivary SCN estimation was done by the Denson analysis. The comparison of salivary SCN level for two groups was statistically compared using unpaired Student's Test. Patient's smoking history (number of cigarettes smoked, duration of smoking) was noted in pack-years. Results: Salivary thiocyanate levels (mM/L) were found to be significantly higher (P < 0.001) in smokers with leukoplakia (13.55 ± 2.58) as compared to smokers without leukoplakia (7.46 ± 1.85). Comparison of salivary thiocyanate levels (mM/L) with pack-years among smokers showed a positive correlation with P < 0.001 which was highly statistically significant. There was a progressive increase in mean salivary thiocyanate levels as the pack-years increased. Conclusion: Salivary SCN level in smokers with leukoplakia is significant high in comparison to smokers without leukoplakia.